New trends in research skills development of future teachers: quantitative approach and empirical studies - Shadiyar Altynbekov; Marzhan Abdualiyeva; Nurgali Ashirbayev; Yerlan Torebek; Azimkhan Abzhapbarov; Zhansaya Ashirbayeva (International Journal of Evaluation and Research in Education (IJERE), 2024)
The purpose of this study was to investigate the relationship between the use of technology and the development of research skills in future teachers, specifically current graduate students participating in Mathematical Olympiads. The study used a quantitative approach and analyzed data collected through a survey. The findings indicated that quantitative analysis skills, problem-solving skills, communication skills, and research methodology skills are the dimensions of research skills in future teachers. The results showed that the use of digital tools for literature searching and curation, online courses and workshops (OCWs), collaborative learning and discussion forums, and data analysis software significantly and positively affected research skills. However, the study failed to provide evidence that digital portfolios (DPs) affected research skills. The limitations of the study and recommendations for future research are discussed. In conclusion, the findings highlight the importance of technology in the development of research skills in future teachers and suggest that technology-based learning resources and tools should be integrated into teacher training programs.